Supraventricular Tachycardia in an Adolescent with Diabetic Ketoacidosis, Severe Hyperkalemia, and Pneumonia: A Case Report from a District Hospital in Indonesia - Desty Fahriska; Muhammad Rahmatsyah Nasution; Nur Robbiyah (International Medical Journal Corp. Ltd, 2026)
Introduction: Diabetic ketoacidosis (DKA) is a major cause of morbidity and mortality in children with type 1 diabetes mellitus (T1DM). Although electrolyte disturbances are common, life-threatening arrhythmias such as supraventricular tachycardia (SVT) are rarely reported, especially in resource-limited settings. This case illustrates the successful management of SVT triggered by severe hyperkalemia during DKA. Case Illustration: A 14-year-old girl with known T1DM presented with unconsciousness, Kussmaul breathing, and a three-day history of fever, cough, and vomiting. Initial assessment revealed Glasgow Coma Scale 9/10, heart rate 158 bpm, and blood pressure 113/64 mmHg. Laboratory findings showed blood glucose 425 mg/dL, pH 6.92, bicarbonate 3.4 mmol/L, and potassium 8.2 mmol/L. Serial electrocardiograms (ECG) showed peaked T-waves followed by narrow-complex SVT. Due to unavailability of adenosine, a vagal maneuver using an ice pack on the face was performed, along with intravenous calcium gluconate and insulin drip. The rhythm converted to sinus tachycardia within minutes. The patient also had bronchopneumonia and parotitis as DKA precipitants. Recovery was uneventful with no arrhythmia recurrence. Discussion: Hyperkalemia in DKA results from insulin deficiency, acidosis, and transcellular potassium shift. It can cause peaked T-waves and re-entrant arrhythmias including SVT. Vagal maneuvers are first-line for stable pediatric SVT. Calcium gluconate stabilizes cardiac membranes, while insulin and rehydration correct hyperkalemia. Conclusion: In DKA with hyperkalemia, early ECG monitoring is essential to detect arrhythmias. Vagal maneuvers can be effective even without adenosine. Stepwise management is life-saving.